D3, the new diffractometer for the macromolecular crystallography beamlines of the Swiss Light Source. (3rd February 2014) - Fuchs, Martin R.; Pradervand, Claude; Thominet, Vincent; Schneider, Roman; Panepucci, Ezequiel; Grunder, Marcel; Gabadinho, Jose; Dworkowski, Florian S. N.; Tomizaki, Takashi; Schneider, Jörg; Mayer, Aline; Curtin, Adrian; et al.
<x xml:space="preserve">Abstract</x> A new diffractometer for microcrystallography has been developed for the three macromolecular crystallography beamlines of the Swiss Light Source. Building upon and critically extending previous developments realised for the high‐resolution endstations of the two undulator beamlines X06SA and X10SA, as well as the super‐bend dipole beamline X06DA, the new diffractometer was designed to the following core design goals. (i) Redesign of the goniometer to a sub‐micrometer peak‐to‐peak cylinder of confusion for the horizontal single axis. Crystal sizes down to at least 5 µm and advanced sample‐rastering and scanning modes are supported. In addition, it can accommodate the new multi‐axis goniometer PRIGo (Parallel Robotics Inspired Goniometer). (ii) A rapid‐change beam‐shaping element system with aperture sizes down to a minimum of 10 µm for microcrystallography measurements. (iii) Integration of the on‐axis microspectrophotometer MS3 for microscopic sample imaging with 1 µm image resolution. Its multi‐mode optical spectroscopy module is always online and supports in situ UV/Vis absorption, fluorescence and Raman spectroscopy. (iv) High stability of the sample environment by a mineral cast support construction and by close containment of the cryo‐stream. Further features are the support for in situ crystallization plate screening and a minimal achievable detector distance of 120 mm for the Pilatus 6M, 2M and the macromolecular crystallography group's planned future area detector Eiger 16M.